Pengalaman Mahasiswa Pekerja dalam Pembelajaran Hybrid: Studi Kasus di Sekolah Tinggi Ilmu Ekonomi Balikpapan - Anhar, Anhar; Rezki, Faizah Mualaf Fania; Rahmadani, Fitri; Shabah, Jernie Aliefa; Erianty, Najwa Nabila; Sari, Ratna (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the experiences of working students in hybrid learning at higher education institutions by highlighting the challenges, strategies, adaptations, and their implications. The study uses an interpretative phenomenological analysis (IPA) qualitative approach, with participants being early-semester students who work part-time. Data were collected through interviews, observations, and diary entries, then analyzed based on the six stages of IPA with reference to communication theory, academic integration, and communication anxiety. Data analysis was conducted using the Interpretative Phenomenological Analysis (IPA) approach. Research results show that hybrid learning increases motivation, digital literacy, independence, and time efficiency, but also presents technical, academic, and psychological obstacles, particularly related to time management, communication anxiety, and infrastructure limitations. The success of working students is greatly influenced by individual readiness, lecturer support, social environment, and campus policies. This study concludes that hybrid learning is a relevant and adaptive learning model, but requires a targeted implementation strategy to minimize obstacles